2019
DOI: 10.1002/htj.21513
|View full text |Cite
|
Sign up to set email alerts
|

Entropy analysis for heat transfer in a rectangular channel with suction

Abstract: The purpose for this paper is to study heat transfer in a rectangular channel with suction applied at the adjacent two side walls. A two‐dimensional laminar viscous fluid flow is generated due to the application of suction/injection. The other two opposite sides are kept at a constant temperatures, and the walls with suction are maintained at a constant heat flux. The streamlines thus obtained due to the flow and isothermal lines and heat function are analyzed. The regions of high and low frictions are found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Of applied character, in solving the conjugated problems of hydrodynamics and thermal exchange, is the series of papers that employ a joint solution to the equations of motion and energy [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. If one examines, in the problem on a medium's motion in a cavity, the joint effect of the fields of speed, pressure, and temperature, a given problem then could be applied when the heat exchange is intensified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Of applied character, in solving the conjugated problems of hydrodynamics and thermal exchange, is the series of papers that employ a joint solution to the equations of motion and energy [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. If one examines, in the problem on a medium's motion in a cavity, the joint effect of the fields of speed, pressure, and temperature, a given problem then could be applied when the heat exchange is intensified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Of interest is a study reported in work [14] into the effect of flow control on heat exchange in a three-dimensional rectangular cavity. The authors established patterns in current lines, isotherms, and identified regions with the maximum and minimum energy dissipation values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%